Scanning Blade of Propeller Using Laser Scanning Probe - Andrealin (NIM : 13112092), Helwin
Laser scanning probe is one of the probes that can be used to perform scanning on freeform objects using coordinate measuring machine. Result of scanning is dots on the space known as point cloud. Point cloud will be processed into mesh. Mesh can be rated with 4 parameters, namely noisy, density, completeness, and accuracy. These parameters are used to perform an optimization to get the mesh that is considered to represent the actual object. The mesh that is considered the most representative of the actual object is then processed into solid to obtain the model of the object. In this final project, the scanning process parameters chosen to be optimized are inplane incident angle, outplane incident angle, point distance (point and stripe value), and overlap value. In point cloud processing, data processing, ie filtering, meshing, global remesh, defect repair, and hole repair, will be seen its influence to the quality of mesh data. After scanning with different parameters, scans with inplane incident angle 45°, outplane incident angle 45°, 0.0 point value, and 0.05 stripe value have the best quality. Overlap value does not affect quality. The processing of the scan results should be done to improve the scan results to get the most representative model.